Intratumoral Translocation Positive Heterogeneity in Pediatric Alveolar Rhabdomyosarcoma Tumors Correlates to Patient Survival Prognosis - Gleditsch, Katrina; Peñas, Jorge; Mercer, Danielle; Umrigar, Ayesha; Briscoe, James; Stark, Matthew; Tsien, Fern; Hollenbach, Andrew D. (Frontiers in Cell and Developmental Biology, 2020)
Alveolar rhabdomyosarcoma (ARMS) is characterized by one of three translocation states: t(2;13)(p35;p14) producing PAX3-FOXO1, t(1;13)(p35;q14) producing PAX7-FOXO1, or translocation-negative. Tumors with t(2;13) are associated with greater disease severity and mortality than t(1;13) positive or translocation negative patients. Consistent with this fact, previous work concluded that a molecular analysis of RMS translocation status is essential for the accurate determination of prognosis and diagnosis. However, despite this knowledge, most diagnoses rely on histology and in some cases utilize fluorescence in situ hybridization (FISH) probes unable to differentiate between translocation products. Further, diagnostic RT-PCR analysis, which can differentiate translocation status, is unable to determine intratumoral translocation heterogeneity, making it difficult to determine if heterogeneity exists and whether correlations exist between this heterogeneity and patient outcomes. Using newly developed FISH probes, we demonstrate that intratumoral heterogeneity exists in ARMS tumors with respect to the presence or absence of the translocation product. We found between 3 – 98% of cells within individual tumor samples contained a translocation event. Further, we demonstrate a significant inverse correlation (R2 = 0.66, p = 0.001) between the extent of intratumoral translocation heterogeneity and failure-free survival of patients. Taken together, these results provide further support for the inclusion of the molecular analysis of these tumors, and expand on this idea to support also determining the extent of intratumoral translocation heterogeneity in the diagnosis of ARMS to improve diagnostic and prognostic indicators for patients with these tumors.